Evaluation of Contact Center Academy for PT Infomedia Nusantara as a New Business Idea - Purba, Dify Martua Togi; Rudito, Priyantono (The Indonesian Journal of Business Administration, 2012)
Contact center is a very important service for companies to response and answers customer problem and questions, the example of contact center channel such as, telephone, short text messaging, website, chat, walk-in center, and other media which related to customers. Contact center is vital for companies, the problem occurs is the level of turnover in contact center industry is quite high, and the fulfillment of labor is very slow and difficult, as well as the communication skills of contact center workforce is not meet the standard, then led many companies derive bad image from the customers.To fulfilling contact center workforce that has a good ability to serve its customers as well as well trained on the ins and outs of contact center technology, contact center academy as institution is needed to enhance their knowledge and also the ability for workers in contact center.In this final project, the data collection method is done by distributing the questionnaires to labor in contact center industry and company that has a contact center, and based on the analysis of the issues raised in PT Infomedia Nusantara.From all the data that has been collected by the author, as well as actual problems occur, the solution given by the author is contact center academy as an institution to enhance the capabilities of the contact center workers as well as not only the to improve the services, but as a new business opportunity for PT Infomedia Nusantara, which currently has more than 12,000 agents and also a lot of companies who manage their own contact center.. Keywords: academy, contact center